2015
DOI: 10.1021/ja510711x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Versipelostatin: Identification of an Enzyme-Catalyzed [4+2]-Cycloaddition Required for Macrocyclization of Spirotetronate-Containing Polyketides

Abstract: Versipelostatin (VST) is an unusual 17-membered macrocyclic polyketide product that contains a spirotetronate skeleton. In this study, the entire VST biosynthetic gene cluster (vst) spanning 108 kb from Streptomyces versipellis 4083-SVS6 was identified by heterologous expression using a bacterial artificial chromosome vector. Here, we demonstrate that an enzyme, VstJ, catalyzes the stereoselective [4+2]-cycloaddition between the conjugated diene and the exocyclic olefin of a newly identified tetronate-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 30 publications
(48 reference statements)
0
92
0
2
Order By: Relevance
“…The biosynthetic mechanism of the spirotetronate-class antibiotics has been shown to include a polyketide assembly line, a glycerate utilization system, a sugar modification, and a novel [4 þ 2]-cycloaddition system for the spirotetronate skeleton (5,16).…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthetic mechanism of the spirotetronate-class antibiotics has been shown to include a polyketide assembly line, a glycerate utilization system, a sugar modification, and a novel [4 þ 2]-cycloaddition system for the spirotetronate skeleton (5,16).…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding a transcriptional regulator of the TetR family and an MFS transporter are well-conserved among the gene clusters of maklamicin, chlorothricin, kijanimicin, and tetrocarcin A, suggesting that these two genes, in addition to the biosynthetic genes for the polyketide backbone and the tetronate moiety, play a common role in the production of the spirotetronates. The recent studies reported intriguing enzymes for performing a Diels-Alder reaction, which demonstrated that VstJ catalyzes the stereoselective [4 + 2]-cycloaddition for the formation of spirotetronate structure in the versipelostatin biosynthesis (Hashimoto et al 2015), and that ChlE3 is a dialkyldecalin synthase and ChlL is a spiro-conjugate synthase in the chlorothricin biosynthesis (Tian et al 2015). These findings strongly suggest that Orf23, a homologue of VstJ and ChlL, catalyzes the formation of cyclohexene unit in the maklamicin biosynthesis and that MakC1, a ChlE3 homologue, catalyzes the formation of trans-decalin moiety.…”
Section: Discussionmentioning
confidence: 99%
“…32 The homologous VstJ identified in the biosynthetic gene cluster of 12 was also functionally characterized. 33 Interestingly, function of PyrI4 was complemented with the homologous enzyme ChlL from the 13 gene cluster, 32 suggesting that these enzymes accepted the substrates with various chain lengths and substituent. Scheme 4 Biogenesis of spirotetronate/spirotetramate superfamily of natural products.…”
Section: Intramolecular Daases Generating Unique Molecular Skeletons mentioning
confidence: 99%
“…This released product from active site, thus avoiding product inhibition. Among nine PyrI4 homologs involving related antibiotic biosynthesis, 49 recently characterized DAase VstJ lacked the lid-like N-terminal sequence, 33 suggesting that catalytic mechanism is variable in each DAase of this family.…”
Section: Recent Advances Of Diels-alderases a Minami And H Oikawamentioning
confidence: 99%